Accuracy of risk tools to predict critical bleeding in major trauma: A systematic review with meta-analysis. Issue 6 (14th June 2022) - Gianola, Silvia; Castellini, Greta; Biffi, Annalisa; Porcu, Gloria; Napoletano, Antonello; Coclite, Daniela; D'Angelo, Daniela; Fauci, Alice Josephine; Iacorossi, Laura; Latina, Roberto; Salomone, Katia; Gupta, Shailvi; et al.
Abstract : BACKGROUND: Early detection of critical bleeding by accurate tools can help ensure rapid delivery of blood products to improve outcomes in major trauma patients. We conducted a systematic review to evaluate the accuracy of risk tools to predict critical bleeding in patients with major trauma. METHODS: PubMed, Embase, and CENTRAL were searched up to February 2021 for studies investigating risk tools to predict critical bleeding for major trauma people in prehospital and emergency department. We followed the Preferred Reporting Items for Systematic Review and Meta-Analysis of Diagnostic Test Accuracy study guidelines. Two independent authors included studies, extracted data, appraised the quality using the Quality Assessment of Diagnostic Accuracy Studies 2 and assessed the certainty of evidence (CoE) using the Grading of Recommendations Assessment, Development and Evaluation methodology. Sensitivity, specificity, and the receiver operating characteristics curve for all selected triage tools. RESULTS: Eighty-nine observational studies for adults and 12 observational studies for children met our inclusion criteria. In adults, we found 23 externally validated and 28 unvalidated tools; in children, 3 externally validated tools and 5 unvalidated. In the externally validated tools, we identified those including clinical, laboratory, and ultrasound assessments. Among tools including only a clinical assessment, the Shock Index showed high sensitivity and specificity with the CoE ranging from very low to moderate in adults, as well as Shock Index Pediatric Age adjusted with a moderate CoE. We found that tools using clinical, laboratory, and ultrasound assessments were overall more accurate than those tools without all three components. CONCLUSION: Clinicians should consider risk tools to predict critical bleeding in a time-sensitive setting like major life-threatening trauma. The Shock Index and Shock Index Pediatric Age adjusted are easy and handy tools to predict critical bleeding in the prehospital setting. In the emergency department, however, many other tools can be used, which include laboratory and ultrasound assessments, depending on staff experience and resources. LEVEL OF EVIDENCE: Systematic Review and Meta-Analysis; Level III.